Golden Thistle (scolymus Hispanicus L.) Hydromethanolic Extracts Ameliorated Glucose Absorption and Inflammatory Markers in Vitro - Güleç, Şükrü; Özel Taşcı, Cansu; Güleç, Şükrü (Wiley, 2023)
Golden thistle (GT, Scolymus hispanicus L.) is an edible plant native to the Mediterranean. Several activities have been reported for the GT, as it is used for traditional medicinal purposes in some cultures. In this study, we aimed to investigate the effects of GT crude extract on phenolic bioavailability, antidiabetic, and anti-inflammatory activities by using colonic epithelium (CaCo-2) and murine macrophage (RAW 264.7) cell lines. The CaCo-2 cells were grown on the bicameral membrane system for intestinal bioavailability and glucose efflux. Lipopolysaccharide (LPS, 0.5 mu g/mL) was used to induce systemic inflammation on RAW 264.7. The inflammatory medium of RAW 264.7 cells was given to Caco-2 cells to mimic colonic inflammation. Our results showed that 5-o-caffeoylquinic acid had an apparent permeability of (1.82 +/- 0.07) x 10-6 cm/s after 6 h. The extract lowered the glucose efflux by 39.4%-42.6%, in addition to the reductions in relative GLUT2 mRNA expressions by 49%-66% in pre- and co-treatments (p < .05). Decreases in systemic inflammation markers of nitric oxide, tumor necrosis factor-alpha, and interleukin-6 (IL-6) were also detected in 30%-45% range after pre-treatments with the GT extract (p < .05). Lastly, colonic inflammation markers of IL-6 and IL-8 were reduced by 8.7%-19.5% as a result of GT pre-treatments (p < .05). Thus, an in vitro investigation of GT extract revealed promising results on antidiabetic and anti-inflammatory activities.
Article; Early Access
Keywords: Antidiabetic activity; Colonic inflammation; Golden thistle; Scolymus hispanicus L.; Systemic inflammation